2022
DOI: 10.1186/s41983-022-00455-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, clinical, and biochemical aspects of patients with Alzheimer disease

Abstract: Background The most common form of dementia is Alzheimer’s disease (AD). The clinical manifestations of AD are loss of memory that is progressive and deterioration in cognitive function. The objective of this study is to find patterns of AD among patients regarding clinical aspects, psychological aspects, and laboratory aspects, as well as to determine the role of some genes (APOE1, APOE2, and TMEM106B) in the pathogenesis of AD. In this case–control study, 40 patients with AD were recruited fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…It has been observed that the level of acetylcholine is decreased in patients with AD. [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] Therefore, drugs that can increase acetylcholine levels are useful in the management of patients with AD. Regulatory authorities across the globe have approved acetylcholinesterase inhibitors for the treatment of patients with AD.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the level of acetylcholine is decreased in patients with AD. [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] Therefore, drugs that can increase acetylcholine levels are useful in the management of patients with AD. Regulatory authorities across the globe have approved acetylcholinesterase inhibitors for the treatment of patients with AD.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive impairment (CI) is a multifactorial entity caused by genetic, environmental, and biological factors interacting differently in each individual [ 1 , 2 , 3 ]. Several clinical, pathological [ 4 , 5 ], and biomarkers studies [ 6 ] have suggested that specific individuals may show signs of CI while others remain asymptomatic regardless of having similar disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…Manual work, especially when it includes the creation of commodities, has been linked to an increased risk of clinical Alzheimer's disease [31]. There are also studies about risk factors, pathogenesis, and structural and functional changes associated with neurodegeneration in AD [32][33][34], the genetic, clinical, and biochemical data of individual patients [35], searching for peripheral biomarkers in neurodegenerative diseases [36] and gut microbiota regulation and their implication in the development of neurodegenerative disease [37,38]. In [39], the pathophysiological basis and biomarkers of AD pathology, and molecular signs of neural inflammation in neurodegenerative diseases are investigated.…”
Section: Introductionmentioning
confidence: 99%